Impact of a diagnostics-driven antifungal stewardship programme in a UK tertiary referral teaching hospital. (24th September 2018) - Rautemaa-Richardson, R; Rautemaa, V; Al-Wathiqi, F; Moore, C B; Craig, L; Felton, T W; Muldoon, E G
Abstract: Objectives: A concise invasive candidosis guideline (based on the ESCMID candidaemia guideline) utilizing an informative biomarker [serum β-1–3-d -glucan (BDG)] was developed in 2013 by an antifungal stewardship (AFS) team and implemented with the help of an AFS champion in 2014. The main aims of the AFS programme were to reduce inappropriate use of antifungals and improve patient outcomes. The aim of this project was to evaluate the compliance of the ICU teams with the invasive candidosis guideline and the impact of the AFS programme on mortality and antifungal consumption on the ICUs (total of 71 beds). Methods: All patients who were prescribed micafungin for suspected or proven invasive candidosis during 4 month audit periods in 2014 and 2016 were included. Prescriptions and patient records were reviewed against the guideline. Antifungal consumption and mortality data were analysed. Results: The number of patients treated for invasive candidosis decreased from 39 in 2014 to 29 in 2016. This was mainly due to the reduction in patients initiated on antifungal therapy inappropriately: 18 in 2014 and 2 in 2016. Antifungal therapy was stopped following negative biomarker results in 12 patients in 2014 and 10 patients in 2016. Crude mortality due to proven or probable invasive candidosis decreased to 19% from 45% over the period 2003–07. Antifungal consumption reduced by 49% from 2014 to 2016. Conclusions: The AFS programme was successful in reducing the number of inappropriate initiations of antifungals by 90%. Concurrently, mortality due to invasive candidosis was reduced by 58%. BDG testing can guide safe cessation of antifungals in ICU patients at risk of invasive candidosis.